IDENTIFIKASI KARAKTERISTIK ALAT PENCERNAAN KELELAWAR PTEROPUS ALECTO DI SULAWESI BAGIAN UTARA - Pendong, Leo K.; Umboh, J. F; Imbar, M; Rahasia, C A (ZOOTEC, 2015)
CHARACTERISTICS IDENTIFY OF THE DIGESTIVE ORGANS OF BAT (PTEROPUS ALECTO) IN NORTHERN SULAWESI. The study aimed to classify Pteropus alecto (Black flying foxes=paniki yaki), based on the type of feed and the digestive system. A Descriptive explorative method was used in this study. The primary data, consist of animals sample, and of laboratory identification of the shapes physical morphology  and size of digestive organs. The secondary data was taken by collecting the information from bat origin region, or its habitat. The results showed, the general characteristics of bat (Pteropus alecto), both male and female were performed a hairy color black in all parts of  the body (except in the wings), it has no tail, the face shape resembles a dog or fox, has sharp curved claws on thumb, also on both toes, for hanging. The body length of the observed P. alecto were ±16.4 cm (♀) and ±22.5 cm (♂), with the body weight was ± 719,87 g on male, heavier than females  (± 526.5 g). The profiles gastrointestinal organs of bat, viz: the teeth, stomach, intestine, and colon. Yhe teeth formula, were I = 2/2; C = 1/1; Pm = 2/2; M = 3/4, the number of overall teeth were 34. The digestive tract organs of bat (P. alecto) were suspected bigger, longer, and heavier, than other frugivore bat types, where the length of the stomach were ± 8.45 cm (♂) and 8.04 (♀), the length of the small intestine were ± 289.3 cm (♀) and 302.42 cm (♂), and the colon were ± 24.13 cm (♀) and 27.3 cm (♂). The mostly feed types being eaten by P. alecto, namely: papaya (Carica papaya), banana (Musa paradisica), mango (Mangifera indica), soursop (Annona muricata), guava (Psidium guajava) and coconut flower (Cocos nucifera) It is oncluded, bat (Pteropus alecto) has a digestive organs system which generally similar to other monogastric animals, but it has no cecum, and no space for fermentative digestion, and where it main feed is fruits, so it can be categorized as frugivores herbivores monogastric animal (non pseudo-ruminant). Keywords: Pteropus alecto, feed type, digestive tract organs